Electrospun V2O5 nanofibers for energy storage - Soh, Huan Zhong. (2010)
Vanadium pentoxide (V2O5) nanofibers were synthesized through simple electrospinning method, and further demonstrated as an effective material for the electrodes of super capacitors. The effect of annealing temperature on the microstructure and morphology of V2O5 nanofibers is investigated systematically through scanning electron microscopy (SEM), X-ray diffraction (XRD) and Brunauer-Emmett-Teller (BET) surface area measurement. Electrochemical properties of the synthesized products as electrodes in a super capacitor device were studied using cyclic voltammetry (CV), galvanostatic charge/discharge in aqueous electrolyte of different pH and also organic electrolyte. The highest specific capacitance was achieved for V2O5 nanofibers annealed at 400° C, which yielded 190 Fg-1 in aqueous electroyte (2 M KCl) and 250 Fg-1 in organic electrolyte (1 M LiClO4) with promising energy density of 5 Wh kg-1 and 78 Wh kg-1 respectively.